Extracellular superoxide dismutase deficiency impairs wound healing in advanced age by reducing neovascularization and fibroblast function. Issue 3 (10th February 2016) - Fujiwara, Toshihiro; Duscher, Dominik; Rustad, Kristine C.; Kosaraju, Revanth; Rodrigues, Melanie; Whittam, Alexander J.; Januszyk, Michael; Maan, Zeshaan N.; Gurtner, Geoffrey C.
Abstract: Advanced age is characterized by impairments in wound healing, and evidence is accumulating that this may be due in part to a concomitant increase in oxidative stress. Extended exposure to reactive oxygen species (ROS) is thought to lead to cellular dysfunction and organismal death via the destructive oxidation of intra‐cellular proteins, lipids and nucleic acids. Extracellular superoxide dismutase (ecSOD/SOD3) is a prime antioxidant enzyme in the extracellular space that eliminates ROS. Here, we demonstrate that reduced SOD3 levels contribute to healing impairments in aged mice. These impairments include delayed wound closure, reduced neovascularization, impaired fibroblast proliferation and increased neutrophil recruitment. We further establish that SOD3 KO and aged fibroblasts both display reduced production of TGF‐ β 1, leading to decreased differentiation of fibroblasts into myofibroblasts. Taken together, these results suggest that wound healing impairments in ageing are associated with increased levels of ROS, decreased SOD3 expression and impaired extracellular oxidative stress regulation. Our results identify SOD3 as a possible target to correct age‐related cellular dysfunction in wound healing.